Literacy in Digital Reproductive Health: Analysis of Sexual Violence Prevention Among Adolescents in Padangsidempuan City, Indonesia - Elvi Suryani (International Journal of Community Service (IJCS), 2026)
Adolescents in Indonesia increasingly navigate a digitized environment where online and offline risks to sexual and reproductive health intersect. Padangsidimpuan City in North Sumatra has a predominantly young population, yet little evidence exists on how digital reproductive health literacy can be leveraged to prevent sexual violence. This qualitative study adopts a narrative review and document-based content analysis to synthesize empirical and conceptual literature on digital health literacy, adolescent reproductive health education, and sexual and technology-facilitated gender-based violence in Indonesia, with a specific focus on implications for Padangsidimpuan. Data sources include peer‑reviewed journals, government statistics, and policy and NGO reports. The analysis identifies four major themes: (1) rapid digitalization and youth demographics as a double-edged sword, (2) persistent gaps in reproductive health literacy and taboo-laden communication, (3) the high and evolving burden of sexual and online gender-based violence among adolescents, and (4) digital reproductive health literacy as a promising but underutilized strategy for primary prevention. A multi-level framework is proposed, emphasizing the roles of schools, families, health services—especially midwives—and local government in strengthening adolescents’ critical, safe, and rights-based engagement with digital reproductive health information. The findings inform context-sensitive strategies for Padangsidimpuan and highlight priorities for future local qualitative research